Enhancing biodesulfurization by engineering a synthetic dibenzothiophene mineralization pathway - Martínez, Igor; Mohamed, Magdy El-Said; García, José Luis; Díaz, Eduardo (Frontiers in Microbiology, 2022)
A synthetic dibenzothiophene (DBT) mineralization pathway has been engineered in recombinant cells of Pseudomonas azelaica Aramco J strain for its use in biodesulfurization of thiophenic compounds and crude oil. This functional pathway consists of a combination of a recombinant 4S pathway responsible for the conversion of DBT into 2-hydroxybiphenyl (2HBP) and a 2HBP mineralization pathway that is naturally present in the parental P. azelaica Aramco J strain. This novel approach allows overcoming one of the major bottlenecks of the biodesulfurization process, i.e., the feedback inhibitory effect of 2HBP on the 4S pathway enzymes. Resting cells-based biodesulfurization assays using DBT as a sulfur source showed that the 2HBP generated from the 4S pathway is subsequently metabolized by the cell, yielding an increase of 100% in DBT removal with respect to previously optimized Pseudomonas putida biodesulfurizing strains. Moreover, the recombinant P. azelaica Aramco J strain was able to use DBT as a carbon source, representing the best characterized biocatalyst harbouring a DBT mineralization pathway and constituting a suitable candidate to develop future bioremediation/bioconversion strategies for oil-contaminated sites.